Effect of dietary supplementation of L-glutamine and L-glutamic on acute phase protein and heat shock protein 70 responses to heat stress in broiler chickens - Olubodun, Joshua Omolayo; Idrus, Zulkifli; Kasim, Azhar; Bejo, Mohd Hair (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2013)
Broiler chickens were fed 0.5% AminoGut (AG) (contained a mixture of L-Glutamine and L-Glutamic) for various durations and subjected to either 34oC (4 hours daily from day 21-42) or 24oC. Heat treatment and AG supplementation increased heat shock protein (HSP) 70 expression in the liver and duodenum on day 42. Serum concentration of ceruloplasmin was neither affected by heat nor AG supplementation. It was concluded that AG supplementation may improve heat tolerance in broiler chickens through elicitation of HSP70 reaction.